PENGARUH PERENCANAAN ANGGARAN DAN KETERSEDIAAN ANGGARAN KAS TEHADAP OPTIMALISASI REALISASI PENYERAPAN ANGGARAN PADA PEMERINTAH DAERAH KABUPATEN BALANGAN - Mustakim Mustakim; Rahmi Widyanti; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The purpose of this study was to examine and analyze: (1) The partial effect of Budget Planning on the Optimization of Budget Absorption Realization in the Balangan Regency Government, (2) the partial influence of Cash Budget Availability on the Optimization of Budget Absorption Realization in the Balangan Regency Government (3) Simultaneous influence of Budget Planning and Availability of Cash Budget on the Optimization of Budget Absorption Realization in the Balangan Regency Government.This research was conducted at the Regional Government of Balangan Regency. This type of research is an explanatory research using a quantitative approach. The population in this study were financial managers at 22 Regional Work Units (SKPD) in the Balangan Regency Government. The sampling technique used the saturated sample technique, namely 66 people consisting of 3 financial managers in 22 Regional Work Units (SKPD).data was obtained from the questionnaire results and processed by data analysis techniques using the SPSS (Statistics Program for Social Science) for Windows. Testing the validity using Pearson's Product Moment and for reliability testing using Alpha Cronbach. The classical assumption test uses linearity, normality, heteroscedasticity and multicollinearity tests. Data analysis used multiple linear regression.Based on the results of data analysis shows that: (1) partially there is no significant effect of Budget Planning on the Optimization of Budget Absorption Realization in the Balangan Regency Government, with the value of t arithmetic (0.572) < t table (1.66). In this study, the planning that has been prepared and proposed does not affect the optimal realization of budget absorption. (2) Partially there is a significant effect of the Availability of Cash Budget on the Optimization of Budget Absorption Realization in the Balangan Regency Government, with the value of t arithmetic (2.955) > t table (1.66). The availability of the cash budget greatly influences the optimization of budget absorption in the Balangan Regency Government. (3) Simultaneously there is a significant effect of Budget Planning and Availability of Cash Budget on the Optimization of Budget Absorption Realization in the Balangan Regency Government, with a value of f arithmetic (71,167) > f table (3.14) and a significance of 0.000 < 0.05.